Vivenciar para apreender: o meio ambiente como contexto para o ensino de polímeros - Silva, Márcia Adriana da (2014)
Through the student‟s desinterest and the difficulties in the teaching-learning process of this science, where the teaching methodology employed traditionally is based on the traditional teaching model of transmission-reception in the memorization of concepts, rules, formulas and their applications are prioritized, this work approaches the use of a teaching sequence based on contextualized activities with CTSA approach to the teaching of polymers in high school, as a way to encourage, stimulate and facilitate the learning. Thus, this study investigated the development of contextualized activities with CTSA approach contribute to students understand chemical concepts related to the theme of the waste that is produced in their homes and specially if it provides them, a critical and reflexive positioning on the relationships between Science, Society, Technology and Environment, which are essential for its role as citizens. To this end, various teaching alternatives have been used in order to facilitate learning. Students from the second grade of high school at the Escola Estadual Enoch Garcia Leal studied diverse teaching strategies: lessons dialogued based on discussions of articles published in Revista Química Nova na Escola , experimental activities, instructional material on polymers and field visit to Recycling Plant. As a way of assessing learning, student answered questionnaires. The results indicate that contextualized activities with CTSA approach is a very important recourse that has much to contribute to the training of students, allowing them to reflect on the environmental problems arising from production and improper disposal of waste, as well as relate to the topic, chemical concepts involved on polymers used in everyday life.